REVITALIZING GOTONG ROYONG (MUTUAL COOPERATION) THROUGH THE 80TH INDONESIAN INDEPENDENCE DAY GATE DECORATION CONTEST IN RT 02/RW 08, EAST LABUH BARU DISTRICT, PEKANBARU - Abdul Kudus Zaini; Cyintia Kumalasari; Muhammad Zainal Muttaqin (LPPM ITB AAS Indonesia Surakarta, 2025)
We carried out this community service project in RT 02/RW 08 of East Labuh Baru District, Pekanbaru, to celebrate the 80th anniversary of Indonesian Independence in 2025. The program combined a gate decoration contest with various traditional community games (e.g., tug-of-war, sack races, and pole climbing) and special children’s competitions. These activities served as a vital mechanism for promoting social participation and citizen unity. Our main goal was to strengthen the community’s spirit of mutual cooperation (gotong royong), enhance social solidarity, and instill a deeper sense of nationalism. We used a participatory approach for implementation, involving residents in every stage, from initial planning to final evaluation. The results demonstrated significant success: resident participation reached 95%, the neighborhood became noticeably cleaner and more attractive, and the RT 02/RW 08 residents even secured third place in the District-Level Gate Decoration Contest. This project proves that combining art, sport, and mutual cooperation (gotong royong) through community service effectively strengthens social cohesion and actively fosters a more harmonious character among urban residents